The Influence Of Farmer Characteristics On Beef Cattle Cultivation Competence In Suwawa District, Bone bolango regency - Abdul, Muhamad Fiqkan; Pateda, Sri Yenny; Datau, Fahria; Sahara, La Ode; Laya, Nibras Karnain (International journal of technology and education research, 2026)
The success of beef cattle farming is closely related to the characteristics of farmers, as good character makes it easier for farmers to solve problems related to beef cattle breeding competencies. The purpose of this study is to find out the characteristics of farmers, beef cattle cultivation competence and the influence of farmer characteristics on beef cattle cultivation competence. The research was carried out in Suwawa District, Bone Bolango Regency. The research method used is the survey method The sample determination was carried out by purposive sampling, the number of samples was 54 people spread across 11 villages that are members of the livestock group. The analysis used was a quantitative descriptive analysis, namely to describe the characteristics of farmers and the level of competence of beef cattle cultivation and multiple regression analysis to test the influence of characteristics including age, education, experience and livestock ownership, on beef cattle cultivation competence. The results of the study show that the characteristics of farmers have an average age of 51 years which is classified as productive, the average elementary education is 44.4%, the average livestock business experience is 21 years, the average livestock ownership is 4 heads,. The level of competence of cattle farmers in the aspect of seeds has a score of 144, feed 157 cages, 146 reproduction, and 159 diseases. All aspects are in the good category with an average score of 155. at intervals of 135-175.5 . Variables of education and experience have a positive and significant effect on the competence of beef cattle cultivation, age has a positive but not significant relationship, livestock ownership has a negative and insignificant relationship. Overall, the influence of farmer characteristics on beef cattle cultivation contributed 38%.